Partition-theoretic interpretations of some q-series identities of Ramanujan - Saikia, Nipen (Kuwait Journal of Science, 2021)
Ramanujan's lost notebook contains several $q$-series identities  and some of them have theta-function representations. We give partition-theoretic interpretations of some of these identities  and prove Ramanujan-type congruences for certain partition functions.